Diferentes taxas de infusão de tramadol na analgesia trans e pós-operatória imediata em cães submetidos a procedimentos ortopédicos: Thais Mayara Menegheti.- - Menegheti, Thais Mayara [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Multimodal analgesia is being increasingly used in veterinary medicine and in that context, tramadol has demonstrated effectiveness in controlling moderate to severe pain. The present study aimed to investigate the influence of three rates of tramadol at continuous infusion for trans and post- operative analgesia of dogs undergoing orthopedic surgeries. Further possible changes in cardiovascular and respiratory parameters, side effects as well as analgesia and plasma concentration of tramadol and M1 wee recorded. Thirty dogs were homogeneously distributed according to the surgical procedures and have been subjected to three groups: G1: 2.0 mg/kg/h; G2: 2.5 mg/kg/h; G3: 3 mg/kg/h. Pre-anaesthetic medication in all cases was given intramuscularly with acepromazine (0.04 mg/kg) and tramadol (2.0 mg/kg). Fifteen minutes later, anaesthesia was induced with intravenous propofol (3mg/kg) associated with midazolam (0.2 mg/kg) and maintained with isoflurane. Blood samples were obtained for assessment of serum cortisol and determining plasma concentrations of tramadol and M1. Postoperative analgesia was assessed through the scales University of Melbourne and interval level pain scale for assessment of acute pain in dogs Trans-operative analgesia was sufficient to most animals and the residual analgesia during post-operative period was short. Cardiovascular and respiratory stability were observed, with no adverse effects
Keywords: Analgesia; Cão como animal de laboratorio; Ortopedia veterinaria; Analgesicos; Opioides; Intravenous infusion